2002
DOI: 10.1159/000063628
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunization against Nicotine Suppresses Nicotine-Induced Dopamine Release in the Rat Nucleus accumbens Shell

Abstract: Background: Tobacco smoking is the largest preventable cause of morbidity and premature mortality in the world. Although its medical consequences are well documented, 20–50% of the population even in developed countries remain tobacco smokers. The drugs presently used in smoking cessation have limited efficiency and, therefore, there is a need for alternative and improved treatments. One novel approach in this regard may be provided by immunization against nicotine. Objective: The present study in male Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Coupling haptens to protein carriers typically enhances their immunogenicity. Nicotine conjugates have been successfully used to vaccinate against nicotine [11][12][13][14][15]. Vaccine efficacy in animal models was demonstrated in several different ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupling haptens to protein carriers typically enhances their immunogenicity. Nicotine conjugates have been successfully used to vaccinate against nicotine [11][12][13][14][15]. Vaccine efficacy in animal models was demonstrated in several different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, nicotine concentrations in the brain were lower [11,12,14,15]. The effect on the reward system in brain was demonstrated by suppression of nicotine-induced dopamine release in brains of vaccinated rats [13]. In two animal models, the potential to prevent relapse was investigated: anti-nicotine antibodies prevented the alleviation of abstinence syndromes by nicotine [16] and prevented reinstatement of nicotine-seeking behavior in vaccinated rats [17].…”
Section: Introductionmentioning
confidence: 99%
“…This is a nicotine immunoconjugate IP18-KLH that prevents the access of nicotine to the brain and has demonstrated to reduce the increase in dopamine output in the nucleus accumbens induced by nicotine as well as the reinstatement of nicotine-seeking behavior in rats. It has also been found that IP18-KLH not only did not precipitate but also ameliorate nicotine withdrawal in rats (de Villiers et al, 2010;de Villiers et al, 2002). Therefore, individuals treated with IP18-KLH may even have milder nicotine withdrawal symptoms when they quit smoking.…”
Section: Ip18-klh (Niccine)mentioning
confidence: 99%
“…In rat models of addiction, antibodies induced to cocaine [7][8][9][10] and nicotine [11,12] substantially reduce the amount of these drugs that reaches the brain [13]. Immunization against cocaine and nicotine attenuates self-administration [7] and suppresses dopamine release in the nucleus accumbens shell [13].…”
Section: Introductionmentioning
confidence: 99%
“…Immunization against cocaine and nicotine attenuates self-administration [7] and suppresses dopamine release in the nucleus accumbens shell [13].…”
Section: Introductionmentioning
confidence: 99%